“Cheng Ho, the Admiral of Ming Dynasty and the engagements with the littoral states in the Indian Ocean” - Özay, Mehmet (2023)
Geopolitics has been a natural necessity for historical empires and modern nation-states for each country. Moreover, each state has been forced to have its political resources to overcome the threats and dangers from its geopolitical reality. More than this, there is a philosophical background to each geopolitical initiative. The Ming Dynasty was not an exception to that. The Ming is remembered mostly through the miracle sea voyages, which are regarded as “pioneer status in the world’s maritime history of ocean-going navigation”, led by Cheng Ho, the great eunuch and close assistant to Yung-lo, the third emperor of this Dynasty or the fourth son of Emperor Zhu Yuanghang, the founding father of the Ming Dynasty. He had a determined diplomacy in order to gain the support and collaboration of the foreign countries for the standard and mutual purpose of peace. It is also known that the Yung-lo government’s venture of oceanic voyages was inclusive in its bureaucratic and infrastructural basis. It means that the significant number of staff in almost all relevant professions, including traders, seamen, technicians, etc. belonged to diverse nationalities, including the Muslim one. It is observed that there have been growing narratives about those voyages and their prime actors, their notes under closer scrutinization not only to discover the reality of the maritime power of China at that time but more than this, how and in which scale China had developed and inherited the scientific, technological sources including human resources mainly coming from various nationalities, in particular, the Muslim ones. The narratives extend between two poles, such as admiring the gross body of the Ming navy and the concrete data and information about the geographies and nations along the Indian Ocean visited and revisited by Cheng Ho, who is known as a navigator and diplomat.